Does social capital influence adoption of conservation agriculture among smallholder farmers in Malawi? - Mathanda, H.; Pangapanga-Phiri, I.; Hirpa Tufa, A.; Mangisoni, J.; Alene, A.; Chikoye, D. (International Institute of Tropical Agriculture, 2024)
Reducing Malawi's persistent food insecurity requires increased and sustainable agricultural productivity despite worsening climate shocks and soil degradation. This study focuses on social capital as a catalyst for the uptake of Conservation Agriculture (CA), a sustainable cropping technique that can address these problems. Despite several initiatives from NGOs and the Malawian government, as well as scientific data supporting CA, adoption rates remain below expectations. The study used secondary data collected by the International Institute of Tropical Agriculture (IITA) and the International Maize and Wheat Improvement Centre (CIMMYT) under ‘Understanding and Enhancing the Adoption of Conservation Agriculture in Smallholder Farming Systems of Southern Africa (ACASA) Project’ from 1,512 households sampled randomly. The main objective of this research was to examine how social capital components interact to influence farmers’ decisions in adoption of CA practices using the Negative Binomial Regression Model (NBRM). Principal Component Analysis (PCA) was conducted on social capital elements to derive social capital dimensions. Results show that group membership and relations to leadership positively influenced the adoption of CA. Furthermore, cultivated land, extension services, livestock ownership, and access to credit had a positive influence on the number of CA practices adopted. Although the effect on full CA adoption is minimal compared to partial adoption, results demonstrate favorable trends toward full CA adoption. We also used Seemingly Unrelated Regressions (SUR) to investigate determinants of participation in social networks. Findings show that the number of training a farmer receives is the main determinant across all dimensions of social capital. The results underscore the importance of implementing policies that encourage cooperation and community involvement to strengthen social networks to improve CA uptake.